-
Notifications
You must be signed in to change notification settings - Fork 4
/
Copy pathChap4.tex
250 lines (201 loc) · 8.56 KB
/
Chap4.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
\documentclass[12pt,letterpaper,reqno]{amsart}
\setlength{\oddsidemargin}{.0in}
\setlength{\evensidemargin}{.0in}
\setlength{\textwidth}{6.5in}
\setlength{\topmargin}{-.3in}
\setlength{\headsep}{.20in}
\setlength{\textheight}{9.in}
\usepackage{amsmath}
\usepackage{amsfonts}
\usepackage{amssymb}
\usepackage{amsthm}
\usepackage[all]{xy}
\usepackage{graphicx}
\usepackage{setspace}
\doublespace
%Here are some user-defined notations
\newcommand{\E}{\mathbb E}
\newcommand{\R}{\mathbb R}
\newcommand{\I}{\mathbb I}
%improving spacing in tables (space above and below characters in a row)
\newcommand{\tfix}{\rule{0pt}{2.6ex}}
\newcommand{\bfix}{\rule[-1.2ex]{0pt}{0pt}}
%Here are commands with variable inputs
\newcommand{\intf}[1]{\int_a^b{#1}\,dx}
\newcommand{\intfb}[3]{\int_{#1}^{#2}{#3}\,dx}
\newcommand{\pln}[1]{$\sm${\tt #1}}
\newcommand{\bgn}[1]{$\tt {\sm}begin\{#1\}$}
\newcommand{\nd}[1]{$\tt {\sm}end\{#1\}$}
\newcommand{\marginalfootnote}[1]{%
\footnote{#1}
\marginpar[\hfill{\sf\thefootnote}]{{\sf\thefootnote}}}
\newcommand{\edit}[1]{\marginalfootnote{#1}}
\newtheorem*{wellorder*}{Well Ordering Principle}
%These commands deal with theorem-like environments (i.e., italic)
\theoremstyle{plain}
\newtheorem{theorem}{Theorem}[section]
\newtheorem{corollary}[theorem]{Corollary}
\newtheorem{lemma}[theorem]{Lemma}
\newtheorem{conjecture}[theorem]{Conjecture}
%\newtheorem{wellorder}[theorem]{Well Ordering Principle}
%\newtheorem{equation}{Theorem}[section]
%These deal with definition-like environments (i.e., non-italic)
\theoremstyle{definition}
\newtheorem{definition}[theorem]{Definition}
\newtheorem{example}[theorem]{Example}
\newtheorem{remark}[theorem]{Remark}
\theoremstyle{definition}
\newtheorem{Exercise}{Exercise 4.}
\newtheorem{exercise}{exercise 3.}
%This numbers equations by section
\numberwithin{equation}{section}
%\numberwithin{equation}{Theorem}[section]
%This is for hypertext references
\usepackage{color}
\usepackage{hyperref}
\hypersetup{
colorlinks=true,
linkcolor=blue,
filecolor=blue,
urlcolor=blue,
pdftitle={Overleaf Example},
pdfpagemode=FullScreen,
}
\begin{document}
\author{Zhizhong Pu}
\title{Solutions - Chapter 4}
\date{April 2023}
\maketitle
\thispagestyle{empty}
%% 4.1
\begin{Exercise} For some integer $k$, set $\mu_k=\E[Y^k]$.
(a) Construct an estimator $\hat{\mu_k}$ for $\mu_k$.
Let $Y_i$ be the realized values of random variable $Y$, then the moment estimator $\hat{\mu_k}$ for $\mu_k$ is $\hat{\mu_k} = n^{-1}\sum_{i=1}^n(Y_i^k)$
(b) Show that $\hat{\mu_k}$ is unbiased for $\mu_k$.
\[
\E[\hat{\mu_k}] = n^{-1}n\E[Y_i^k] = \E[Y_i^k] = \mu_k
\]
(c) Calculate $Var(\hat{\mu_k})$. What assumption is needed for $Var(\hat{\mu_k})$ to be finite?
Note that my $\hat{\mu_k}$ can be seen as the single-variable (intercept) linear regression coefficient. Then Theorem 4.3 applies and states that $Var(\hat{\mu_k})<\infty$ iff $2k<n-1+1$ (i.e. $k < \frac{n}{2}$)
(d) Propose an estimator of $Var(\hat{\mu_k})$.
I propose the bias-corrected sample variance:
\[
\widehat{\sigma^2} = \frac{1}{n-1}\sum_{i=1}^n(Y_i^2k-\overline{Y^k})^2
\]
\end{Exercise}
%% 4.2
\begin{Exercise}
\end{Exercise}
%% 4.3
\begin{Exercise} Question see book.
The former is sample mean, which is a random variable, while the latter is population mean / expectation, which is a fixed parameter.
\end{Exercise}
%% 4.4
\begin{Exercise} Question see book.
False. Note: since $X\in \R$, then $\hat{\beta_{OLS} } = \frac{\sum_{i=1}^n X_iY_i}{\sum_{i=1}^n X_i^2} $. Then
\[
\sum_{i=1}^n X_i^2\widehat{e_i} = \sum_{i=1}^n X_i^2(Y_i-X_i\hat{\beta}) = \sum_{i=1}^n X_i^2Y_i - \sum_{i=1}^n (X_i^3 \frac{\sum_{i=1}^n X_iY_i}{\sum_{i=1}^n X_i^2} )
\]
which is not $0$ in general.
\end{Exercise}
% 4.5
\begin{Exercise} Prove (4.20) and (4.21).
(4.20) follows naturally from the unbiasedness property of OLS, as (4.17) specifies the standard OLS model $Y=X\beta+e$. To show (4.21):
\[\begin{split}
Var(\hat{\beta}|X) & = Var((X'X)^{-1}X'Y|X) \\
& = (X'X)^{-1}X' Var(X\beta+e|X) X (X'X)^{-1} \\
& = (X'X)^{-1}X' Var(e|X) X (X'X)^{-1} \\
& = \sigma^2 (X'X)^{-1} (X' \Sigma X) (X'X)^{-1}
\end{split}\]
with the last equation holding for we are given $Var(e|X) = \Sigma \sigma^2 $.
\end{Exercise}
%% 4.6
\begin{Exercise} Prove Theorem 4.5 under the restriction to linear estimators.
For any linear estimator $\Tilde{\beta}$ there must exist $A_{n \times k}$ that is a function of $X$ such that $\Tilde{\beta} = A'Y$. Note that following the OLS G-M Theorem proof, we know that the unbiasedness of $\Tilde{\beta}$ guarantees $A'X=I_k$. Also following the OLS-GM proof:
\[
Var(\Tilde{\beta}|X) = Var(A'Y|X) = A' Var(e|X) A = \sigma^2 A'\Sigma A
\]
with the last equation holding for we are given $Var(e|X) = \Sigma \sigma^2 $.
Now, let $C = \Sigma^{\frac{1}{2}}A - \Sigma^{-\frac{1}{2}} X (X' \Sigma^{-1} X )^{-1} $ so that $ 0 \leqslant C'C = A'\Sigma A - (X' \Sigma^{-1} X)^{-1} $. It follows that
\[
Var(\Tilde{\beta}|X) = \sigma^2 A'\Sigma A \geqslant \sigma^2 (X' \Sigma^{-1} X)^{-1}
\]
\end{Exercise}
%% 4.7
\begin{Exercise}
\end{Exercise}
% 4.8
\begin{Exercise}
\end{Exercise}
% 4.9
\begin{Exercise} Show (4.32) in the homoskedastic regression model.
Note that with homoskedasticity, equation (4.27) holds, which states $\E[\widehat{e_i^2}|X] = (1-h_i)\sigma^2$. Then:
\[\begin{split}
\E[\overline{\sigma^2}|X] & = \E[n^{-1}\sum_{i=1}^n(1-h_i)^{-1}\widehat{e_i^2}|X] \\
& = n^{-1}(1-h_i)^{-1}\sum_{i=1}^n\E[\widehat{e_i^2}|X] \\
& = \sigma^2
\end{split}\]
Note that $(1-h_i)$ can be taken out of conditional expectations on $X$ since $h_i$ is a function of $X$
\end{Exercise}
% 4.10
\begin{Exercise} Prove (4.40)
Recall
\[
V_{\hat{\beta}}^{HC0} = (X'X)^{-1} (\sum_{i=1}^n X_iX_i' \widehat{e_i^2} ) (X'X^{-1})
\]
\[
V_{\hat{\beta}}^{HC2} = (X'X)^{-1} (\sum_{i=1}^n (1-h_i)^{-1} X_iX_i' \widehat{e_i^2} ) (X'X)^{-1}
\]
\[
V_{\hat{\beta}}^{HC3} = (X'X)^{-1} (\sum_{i=1}^n (1-h_i)^{-2} X_iX_i' \widehat{e_i^2} ) (X'X)^{-1}
\]
Then:
\[
V_{\hat{\beta}}^{HC2} - V_{\hat{\beta}}^{HC0} = (X'X)^{-1} [\sum_{i=1}^n ((1-h_i)^{-1} - 1) \widehat{e_i^2} X_iX_i' ] (X'X^{-1})
\]
\[
V_{\hat{\beta}}^{HC3} - V_{\hat{\beta}}^{HC2} = (X'X)^{-1} [\sum_{i=1}^n ((1-h_i)^{-2} - (1-h_i)^{-1} ) \widehat{e_i^2} X_iX_i' ] (X'X^{-1})
\]
Note that $(1-h_i) \in [0,1] $ by Theorem 3.6, so $ (1-h_i)^{-2} \geqslant (1-h_i)^{-1} \geqslant 1 $, then the middle term in each of the last two equations is each a weighted sum of $n$ PSD matrices $X_iX_i'$ with no negative weights. As a result, each middle term is a PSD matrix so
\[
V_{\hat{\beta}}^{HC3} \geqslant V_{\hat{\beta}}^{HC2} \geqslant V_{\hat{\beta}}^{HC0}
\]
\end{Exercise}
% 4.11
\begin{Exercise} Show (4.41) in the homoskedastic regression model, i.e. $\E[V_{\hat{\beta}}^{HC2}|X] = \sigma^2$.
First note that in the book notations, $X'X= \sum X_iX_i'$. Then
\[\begin{split}
\E[V_{\hat{\beta}}^{HC2}|X] & = \E[(X'X)^{-1} (\sum_{i=1}^n (1-h_i)^{-1} X_iX_i' \widehat{e_i^2} |X] \\
& = (X'X)^{-1} ( \sum_{i=1}^n (1-h_i)^{-1} \E[\widehat{e_i^2}|X] X_iX_i' ) (X'X)^{-1} \\
& = (X'X)^{-1} ( \sum_{i=1}^n (1-h_i)^{-1} (1-h_i) \sigma^2 X_iX_i' ) (X'X)^{-1} \\
& = \sigma^2 (X'X)^{-1} ( \sum_{i=1}^n X_iX_i' ) (X'X)^{-1} \\
& = \sigma^2 (X'X)^{-1} (X'X) (X'X)^{-1} \\
& = \sigma^2 (X'X)^{-1}
\end{split}\]
with third equality true due to equation (4.27) under homoskedasticity. Note that $(1-h_i)$ can be taken out of conditional expectations on $X$ since $h_i$ is a function of $X$.
\end{Exercise}
% 4.12
\begin{Exercise}
\end{Exercise}
% 4.13
\begin{Exercise}
\end{Exercise}
% 4.14
\begin{Exercise}
\end{Exercise}
% 4.15
\begin{Exercise} Question see book.
(a) Find $V_{\hat{\beta}} = Var(\widehat{\beta})$.
Since we know $X'X=n\I_k$, which means $(X'X)^{-1} = n^{-1} \I_k$. Also, since we assume an i.i.d. random sample, then $Var(e|X) = \sigma^2 \I $. Now consider the conditional variance:
\[\begin{split}
Var(\widehat{\beta} |X) & = Var( (X'X)^{-1}X'e |X) \\
& = (X'X)^{-1}X' Var(e|X) X(X'X)^{-1} \\
& = n^{-2} X' Var(e|X) X \\
& = \frac{\sigma^2}{n}
\end{split}\]
Then then unconditional variance is given by LOTV:
\[
Var(\widehat{\beta}) = Var(\E[\widehat{\beta}|X] + \E[Var(\widehat{\beta}|X)] = \frac{\sigma^2}{n}
\]
\end{Exercise}
\end{document}